Pregnancy decisions after fetal or perinatal death: systematic review of qualitative research. Issue 12 (23rd December 2019) - Dyer, Eleanor; Bell, Ruth; Graham, Ruth; Rankin, Judith
Abstract : Objectives: To synthesise the findings of qualitative research exploring parents' experiences, views and decisions about becoming pregnant following a perinatal death or fetal loss. Design: Systematic review and meta-synthesis of qualitative research. Data sources: Medline, Web of Science, CINAHL, PsycINFO, ASSIA, Embase, PUBMED, Scopus and Google Scholar. Eligibility criteria: Nine electronic databases were searched using predefined search terms. Articles published in English, in peer-reviewed journals, using qualitative methods to explore the experiences and attitudes of bereaved parents following perinatal or fetal loss, were included. Data extraction and synthesis: Qualitative data relating to first-order and second-order constructs were extracted and synthesised across studies using a thematic analysis. Results: 15 studies were included. Four descriptive themes and 10 subthemes were identified. The descriptive themes were: deciding about subsequent pregnancy, diversity of reactions to the event, social network influences, and planning or timing of subsequent pregnancy. The decision to become pregnant after death is complex and varies between individuals and sometimes within couples. Decisions are often made quickly, in the immediate aftermath of a pregnancy loss, but may evolve over time. Bereaved parents may feel isolated from social networks. Conclusions: There is an opportunity to support parents to prepare for a pregnancy after a fetal or perinatal loss, and conversations may be welcomed at an early stage. Health professionals may play an important role providing support lacking from usual social networks. PROSPERO registration number: CRD42018112839